A SOCIAL SEMIOTIC ANALYSIS ON EMMA WATSON’S HEFORSHE CAMPAIGN SPEECH - Qadafi Ahmad (Asosiasi dosen IDEBAHASA KEPRI, 2020)
This study investigated the social and cultural notions by capturing Emma Watson’s speech on gender equality campaign to find out types of semiotic rules principles which can be applied in formal conditions as well as the function in the speech, by employing the theory of van Leeuwen (2004) on semiotic rules with 5 subcategories. The descriptive qualitative method was used in analyzing the paper, in which the data were collected randomly, then analyzed them with the five theories mentioned above, and drew conclusion based on the findings and discussion. The result of this study was divided into four parts for which it was discovered that four of the five rules were used by the speaker, and one was absent due to her own assumption about the matter and the pressure of being an ambassador. The result also demonstrated the nature of the speech as a mere promotional campaign rather than a start of a bigger movement to solve inequality problem in the society.